Antiatherosclerotic effect of Baccaurea angulate: an under-utilized fruit - Mikail, Maryam Abimbola; Ahmed, Idris Adewale; Ibrahim, Muhammad; Hazali, Norazlanshah; Abdull Rasad, Mohammad Syaiful Bahari; Abdul Ghani, Radiah; Hashim, Ridzwan; Abdul Wahab, Ridhwan; Md Isa, Muhammad Lokman; Draman, Samsul (2014)
INTRODUCTION: Cardiovascular diseases (CVDs) continue to be the single leading cause of deaths globally. Most CVD patients are troubled with a condition known as atherosclerosis. Oxidation of low-density lipoprotein (LDL) and chronic inflammation are the two clinical hallmarks of atherosclerosis. Not only the fruits that are more known to the common man today, promise a good health, but many underutilized fruits are also nutritious and have medicinal properties. Baccaurea angulata (BA), locally known as ‘belimbing dayak’ or ‘belimbing hutan’, as one of the underutilized fruits, is widely distributed in Borneo Island of Malaysia and several other regions of Indonesia. The present study was conducted to investigate the effects of B. angulata whole fruit on lipid peroxidation, antioxidative enzyme activities, inflammatory biomarkers and atherosclerotic plaque formation in rabbits fed high cholesterol diet. MATERIALS AND METHODS: Twenty five male rabbits of New Zealand strain were used and randomly divided into five groups. Group C was fed 1% cholesterol diet; group C1 was fed 1% cholesterol diet + 0.5ml/kg/day BA whole fruit juice; group C2 was fed 1% cholesterol diet + 1ml/kg/day BA whole fruit juice; group C3 was fed 1% cholesterol diet + 1.5ml/kg/day BA whole fruit juice; group N was fed normal pellet. Blood, aortas and livers were collected for analysis after 12 weeks of feeding. RESULTS AND DISCUSSION: B. angulata juice had higher antioxidants and anti-inflammatory activities indicated by the increase in the antioxidant enzymes and decrease in inflammatory biomarkers, respectively. Likewise, B. angulata juice reduced plaque formation in rabbit aortas. CONCLUSION: It can be concluded that B. angulata juice possesses the ability to counterbalance oxidation reaction, boost antioxidant enzymes, inhibit inflammatory biomarkers and reduce atherosclerotic plaque, which in turn could prevent atherosclerosis.